2013
DOI: 10.1523/jneurosci.2454-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Permeable AMPA Receptors in the Nucleus Accumbens Regulate Depression-Like Behaviors in the Chronic Neuropathic Pain State

Abstract: Depression is a salient emotional feature of chronic pain. Depression alters the pain threshold and impairs functional recovery. To date, however, there has been limited understanding of synaptic or circuit mechanisms that regulate depression in the pain state. Here, we demonstrate that depression-like behaviors are induced in a rat model of chronic neuropathic pain. Using this model, we show that chronic pain selectively increases the level of GluA1 subunits of AMPA-type glutamate receptors at the synapses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
130
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 75 publications
9
130
0
Order By: Relevance
“…Consistent with previous results, 29,42,44 we found that SNI surgery produced significant mechanical and cold allodynia in the (spared) sural nerve distribution (fig. 1A and B).…”
Section: Resultssupporting
confidence: 93%
“…Consistent with previous results, 29,42,44 we found that SNI surgery produced significant mechanical and cold allodynia in the (spared) sural nerve distribution (fig. 1A and B).…”
Section: Resultssupporting
confidence: 93%
“…FoxOs have been linked to skeletal muscle atrophy and control of cardiomyocyte size in numerous models (Sandri et al, 2004;Skurk et al, 2005) observed in major depression most commonly occur in the raphe nuclei, nucleus accumbens, anterior cingulated cortex, amygdala and hippocampus (Goffer et al, 2013;Tripp et al, 2011;Underwood et al, 1999;Andrus et al, 2012), but we still need to elucidate whether the change of FoxOs and their related signal pathways could be altered in region specific manner.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In addition, pain signals are transmitted to the amygdala and striatum, which have critical roles in the regulation of emotion. Previous studies have demonstrated that emotional dysfunction induced by persistent pain is related to functional alterations in the frontal cortex, hippocampus and striatum [9][10][11]. Neuronal dysfunction in these regions of the brain is also induced by early life stress [12][13][14].…”
Section: Introductionmentioning
confidence: 99%